MENINGKATKAN PRODUKTIVITAS LANSIA DALAM MEMBUAT TAPLAK MEJA DARI KAIN PERCA MELALUI PELATIHAN DI BHAKTILUHUR MALANG - Klemensia Nini; Maria Imelda Kofi (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2022)
Most people view the elderly as a group that is not productive. Especially if the elderly are accompanied by certain disabilities. Most societies view that at an increasingly advanced age, the individual in question is more troublesome because there is not much they can do. However, the government has paid special attention to the elderly by issuing a Law of the Republic of Indonesia in article 13 of 1998 concerning the welfare of the elderly. This means that the elderly, especially those who are seen as still having potential, should continue to be empowered to remain productive in society. The purpose of this study is to describe 1) the productivity ability of the elderly with special needs before being given training in making tablecloths from patchwork and 2) the productivity ability of the elderly with special needs after being given training in making tablecloths from patchwork. This research includes quantitative research of experimental methods. The design study used the Design of One Group Pretest-Posttest. Meanwhile, the variable used is free, namely training in making tablecloths from patchwork and a bound variable, namely the productivity ability of the elderly. The data were analyzed using descriptive statistics with the presentation of data in the form of tables, graphs, and percentage calculations. The subjects of the study were 2 elderly people with special needs aged 62 years and 67 years. Training activities are carried out as many as 6x with a duration of 60 minutes. The results showed that the ability to make tablecloths from patchwork obtained pre-test values for MS subjects: 47.5% and PS subjects: 57.5%. While the posttest value of MS subjects: 80% and PS subjects: 87.5%. When compared to the pre-test and posttest results, there are changes, which means that there is an increase in the productivity of the elderly after receiving training. This increase is that MS has increased by 32.5% and PS by 30%. The average increase in both subjects was 3.5%.